Review on Vision Based Human Motion Detection Using Deep Learning - Zachariah, Lino; Maharajan, K (2023 4th International Conference on Smart Electronics and Communication (ICOSEC), 2023)
The challenging problems addressed by vision-based human motion recognition and its wide range of potential applications have captured the interest of numerous researchers. These applications encompass simple gesture recognition to intricate analysis of behavior in surveillance systems. Since there was a need for practical, automatic violence detection techniques that looked at the visual information obtained from security cameras placed throughout various locations, the violence detection sector became quite popular in the domain of human motion detection systems. As a result, there is a significant advancement in the methods for representing and recognizing human motion. The focus of this study is to discuss the recent advancements made by researchers in these fields. It offers a comprehensive analysis of the methodologies employed and evaluates the credibility of the various submissions. Additionally, the article offers guidelines on approaching future directions for this application.